(3GdhUjI HGdNJeGJ hGdJgGdjds - (3GHf YGHOjf , eMeO Gejf Hf YeQ Hf YHO GdYRjR GdOeTbj,J (B1252 (3g` s ((3eMeO TgQOdhGQ s)
(3ChdgG (B:s
(3CeG HYO ajbhd eMeO Cejf GdTgjQ HGHf YGHOjf GdeGJQjOj deG hbY ai OeTb hZjQgG GdWGYhf GdYGe s
(3BNQgG (B:s
,(3GdfGS YfgG ZGadhf adJcf Ydi PcQ efc hGddg JYGdi CYde hdg GdMeO Ydi eG Cdge hYdi heUdi Gddg Ydi SjOfG eMeO GdfHi GdCcQe hYdi Bdg hUMHg hSde hbO fLR JMQjQ gPg GdhQjbGJ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B42 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B77s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs